Detecting Large Chromosomal Modifications Using Short Read Data From Genotyping-by-Sequencing - Keilwagen, Jens; Lehnert, Heike; Berner, Thomas; Beier, Sebastian; Scholz, Uwe; Himmelbach, Axel; Stein, Nils; Badaeva, Ekaterina D.; Lang, Daniel; Kilian, Benjamin; Hackauf, Bernd; Perovic, Dragan (Frontiers in Plant Science, 2019)
Markers linked to agronomic traits are of the prerequisite for molecular breeding. Genotyping-by-sequencing (GBS) data enables to detect small polymorphisms including single nucleotide polymorphisms (SNPs) and short insertions or deletions (InDels) that can be used, for instance, for marker-assisted selection, population genetics, and genome-wide association studies. Here, we aim at detecting large chromosomal modifications in barley and wheat based on GBS data. These modifications could be duplications, deletions, substitutions including introgressions as well as alterations of DNA methylation. We demonstrate that GBS coverage analysis is capable to detect Hordeum vulgare/Hordeum bulbosum introgression lines. Furthermore, we identify large chromosomal modifications in barley and wheat collections. Hence, large chromosomal modifications, including introgressions and copy number variations (CNV), can be detected easily and can be used as markers in research and breeding without additional wet-lab experiments.